1999
DOI: 10.1074/jbc.274.52.36905
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Binding Site Residues of the Bovine Cation-dependent Mannose 6-Phosphate Receptor

Abstract: Mannose 6-phosphate receptors (MPRs) deliver soluble acid hydrolases to the lysosome in higher eukaryotic cells. The two MPRs, the cation-dependent MPR (CD-MPR) and the insulin-like growth factor II/cation-independent MPR, carry out this process by binding with high affinity to mannose 6-phosphate residues found on the N-linked oligosaccharides of their ligands. To elucidate the key amino acids involved in conveying this carbohydrate specificity, site-directed mutagenesis studies were conducted on the extracyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…This observation is consistent with the hypothesis that the favorable gain in energy due to the additional hydrogen bonds with the penultimate and prepenultimate ␣1,3-linked mannose rings is offset by the unfavorable electrostatic interaction of the penultimate ring with the receptor as the polar face of the penultimate sugar is buried in the protein ( Fig. 1B) (27). Although differences are seen in the contacts between the receptor and the oligosaccharide (compare Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This observation is consistent with the hypothesis that the favorable gain in energy due to the additional hydrogen bonds with the penultimate and prepenultimate ␣1,3-linked mannose rings is offset by the unfavorable electrostatic interaction of the penultimate ring with the receptor as the polar face of the penultimate sugar is buried in the protein ( Fig. 1B) (27). Although differences are seen in the contacts between the receptor and the oligosaccharide (compare Fig.…”
Section: Resultssupporting
confidence: 79%
“…1, A and D). A comparison with our previous structure of the sCD-MPR complexed with pentamannosyl phosphate (P-Man(␣1,3)Man(␣1,3)Man(␣1,3) Man(␣1,2)Man) (27) (Fig. 1B) revealed that the most striking difference between the two structures is the rotation of the penultimate mannose ring by ϳ90°relative to the corresponding ring in the ␣1,3-linked oligosaccharide (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Four conserved residues (Gln-66, Arg-111, Glu-133, and Tyr-143) of the CD-MPR have been shown previously to be essential for Man-6-P recognition (31). These residues are also conserved in the two high affinity binding sites (i.e.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, this study also revealed that domain 5 exhibits a comparable level of sequence identity to the CD-MPR as observed for domains 3 and 9. Our crystal structures of the CD-MPR (13,27) and domains 1-3 of the CI-MPR (28,29) plus mutagenesis studies (21,30,31) have identified conserved residues that are essential for Man-6-P binding. To evaluate the possibility that domain 5 binds carbohydrate, we performed a structure-based sequence alignment to compare domain 5 with the CD-MPR and domains 3 and 9 of the CI-MPR (see Fig.…”
mentioning
confidence: 99%
“…results in only partial inhibition of carbohydrate binding (16). In the bound state, these seven residues are all within hydrogenbonding distance of the terminal sugar moiety (Fig.…”
Section: Resultsmentioning
confidence: 99%